2009
DOI: 10.2337/dc08-1800
|View full text |Cite
|
Sign up to set email alerts
|

First Nationwide Study of the Prevalence of the Metabolic Syndrome and Optimal Cutoff Points of Waist Circumference in the Middle East

Abstract: OBJECTIVEThe purpose of this study was to provide the first national estimate on the prevalence of the metabolic syndrome and its components and the first ethnic-specific cutoff point for waist circumference in the Eastern Mediterranean Region.RESEARCH DESIGN AND METHODSThis national survey was conducted in 2007 on 3,024 Iranians aged 25–64 years living in urban and rural areas of all 30 provinces in Iran. The metabolic syndrome was defined by different criteria, namely the definition of the National Cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
227
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(252 citation statements)
references
References 18 publications
22
227
2
1
Order By: Relevance
“…Values are expressed as mean and standard deviation or as percentages. *Obesity, BMI ≥ 30·0 kg/m 2 ; abdominal obesity, WC ≥ 89 cm (27) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values are expressed as mean and standard deviation or as percentages. *Obesity, BMI ≥ 30·0 kg/m 2 ; abdominal obesity, WC ≥ 89 cm (27) .…”
Section: Resultsmentioning
confidence: 99%
“…*Obesity, BMI ≥ 30·0 kg/m 2 ; class I, 30·0 ≤ BMI < 34·9 kg/m 2 ; class II, 35·0 ≤ BMI < 39·9 kg/m 2 ; class III, BMI ≥ 40·0 kg/m 2 . †Abdominal obesity: WC ≥ 89 cm in men and ≥91 cm in women (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in studies carried out on adult populations of India and Iran, the prevalence rates of MS varied from 33?7 % to 41 % (21)(22)(23) .…”
Section: Prevalence Of Metabolic Syndrome In the Worldmentioning
confidence: 99%
“…25 Our results are in line with two other studies on Iranian population; the first was a cross-sectional study on men and women aged 35-54 years, which analyzed the cutoff points of anthropometric variables for defining at least two major CVD risk factors by ROC analyses, 13 and the second was a national survey that showed that the cutoff point of WC for predicting at least two other components of the metabolic syndrome was 89 cm for men and 91 cm for women. 39 Lemieux et al 40 also defined the threshold value of B95 cm for WC in both genders and the values of 0.94 in men and 0.88 in women for WHR as corresponding to an accumulation of visceral adipose tissue. Welborn and Dhaliwal 29 reported approximately the same cutoff points in predicting all cause and CVD mortality in an Australian male population and the Asia-Oceania study recently pooled Iranian data with Australians' when comparing probable cutoff points with Asian populations.…”
Section: Obesity Variables To Predict Cardiovascular Events F Hadaeghmentioning
confidence: 99%